A New Species of the Genus Eulophias (Zoarcoidei: Stichaeidae) from Korea - Kwun, Hyuck Joon; Kim, Jin Koo (Zootaxa, 2012)
A new species, Eulophias koreanus, belonging to the family Stichaeidae, suborder Zoarcoidei, is described on the basisof five specimens (70.7–160.7 mm in standard length) collected from the southern sea of Korea. The new species differsfrom the only two known congeneric species, Eulophias tanneri and Eulophias owashii, which are endemic to Japan. Eu-lophias koreanus is readily distinguished from E. tanneri by the numbers of anal-fin rays (102–103 vs. 75 in E. tanneri)and caudal-fin rays (9–10 vs. 7). Eulophias koreanus is more similar to E. owashii than to E. tanneri, but differs from theformer in the number of vertebrae (141–143 vs. 133 in E. owashii) and pectoral-fin length (36.1–39.5% of HL vs. 27.8%).Regarding the caudal skeletons in E. koreanus, the last dorsal pterygiophore is inserted between the last 1st and 2nd or the2nd and 3rd neural spines, and a small spine is absent on the ventral portion of the parhypural, whereas in E. owashii, thelast dorsal pterygiophore is inserted between the last 3rd and 4th neural spines, and a small spine is present on the ventralportion of the parhypural. Analyses of 500-bp sequences of mitochondrial DNA cytochrome oxidase subunit I providestrong evidence that the five new specimens belong to the same species, even though they show some variation in head shape.